Adoption and law : the unique personal experiences of birth mothers in adoption proceedings - Deblasio, Lisamarie (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
Using a socio-legal framework, this book explores the experiences that birth mothers face in state sanctioned adoption proceedings in the UK. Featuring personal, in-depth interviews and conversations with 32 birth mothers, the book highlights perspectives and voices that are seldom the focus in leading discourses of professional practice in this area of law. The book also demands that the statutory rights, support and care of birth mothers are recognised and strengthened.This book delivers a comprehensive insight into many aspects and controversies of legal child adoption, including the development and reform of adoption law over history, giving the reader insight into the deep-rooted political and social tensions around the use of adoption. The uniqueness of birth mothers' subjective stories of adoption contrasts powerfully with the legal theory providing the reader with an intimate paradigm of adoption.The book includes discussion of obiter dicta and authoritative guidance on adoption practice from the Supreme Court and Court of Appeal in Re B (A Child) (Care Proceedings: Appeal) [2013] UKSC 33 and Re B-S (Children) (Adoption: Leave to Oppose) [2013] EWCA Civ 1146. It also considers Court of Appeal's recent ruling on post adoption contact in Re B (A Child) (Post-Adoption Contact) [2019] EWCA Civ 29, the first case to come before the court since section 9 of the Children and Families Act 2014 amended the Adoption and Children Act 2002, with the new insertion of section 51A and 51B providing for court ordered post adoption contact. This book is ideally suited to undergraduate students, as well as a more multi- disciplinary audience.
Adoption Law : history, development and reform -- The adoption and Children Act 2002 : key principles -- The story of birth mothers -- The research methodology, building trust with birth mothers -- Introduction to the findings : the social experiences of birth mothers -- The experiences of birth mothers and the law : before the adoption order -- The experiences of birth mothers and the law : after the adoption order -- The current law and policy on adoption : what does the future hold for birth mothers? -- Redress for operational failures and poor practice in the adoption process.
OCLC-licensed vendor bibliographic record.
Keywords: Adoption -- Law and legislation -- England; Birthmothers -- Legal status, laws, etc. -- England; Great Britain; LAW / Family Law / General; LAW / Family Law / Children; LAW / Child Advocacy